More than half of hip fracture patients do not regain mobility in the first postoperative year. Issue 2 (21st June 2012) - Vochteloo, Anne JH; Moerman, Sophie; Tuinebreijer, Wim E; Maier, Andrea B; de Vries, Mark R; Bloem, Rolf M; Nelissen, Rob GHH; Pilot, Peter
<x xml:space="preserve">Abstract</x> Aim: To measure functional recovery and determine risk factors for failure to return to the prefracture level of mobility of hip fracture patients 1 year postoperatively. Methods: A prospective cohort follow‐up study of 390 hip fracture patients aged 65 years and older was carried out. Patients were stratified in categories based on prefracture mobility: mobile without aid, with aid in‐ and outdoors, or only mobile indoors. Immobile patients were excluded. Risk factors for not regaining prefracture mobility were identified. Results: Nearly half of all patients regained their prefracture level of mobility after 1 year. Mobile patients without an aid were less likely to return to their prefracture mobility level compared with patients who were mobile with aid or mobile indoors. After 1 year, 18.7% of all patients had become immobile. Most important independent risk factors for failure to return to the prefracture level of mobility were a limited prefracture level of activities of daily living and a delirium during admission. Conclusions: The risk not to regain prefracture mobility is highest in mobile patients without an aid. The risk of becoming immobile is higher in those having a lower prefracture mobility. Activities of daily living dependence and delirium were the main risk factors for not regaining mobility. Geriatr Gerontol Int 2013; 13: 334–341.